Frauensatiren der Frühen Neuzeit Traditionen, Topoi, Tendenzen - Brucklacher, Emma Louise (Frühe Neuzeit, 2023)
Bossy broads, lustful virgins, and pseudo-scholarly ladies can be found everywhere in early modern satiric writings. By taking up misogynist traditions/tropes, they prove to have been a significant transgeneric phenomenon of German literature and cultural history during the European querelle des sexes. By looking at how discursive structures function, this volume is the first to systematically address literary constructions of "deviant women."